Stability-indicating methods for the determination of olanzapine in presence of its degradation products - Hussien, Lobna Abd El Aziz; Ghani, Maha Farouk Abdel; El-Alamein, Amal Mahmoud Abo; Mohamed, Ekram Hany (European Journal of Chemistry, 2014)
Simple, sensitive and precise spectrophotometric and chemometric stability indicating techniques were adopted for Olanzapine (OLA) determination in presence of its degradation products over a concentration range of 0.002-0.02 mg/mL. The spectrophotometric technique involves six methods; first method is first derivative (D1) spectrophotometric one, which allows the determination of OLA in presence of its acidic and alkaline degradation products at 261.2 and 260.6 nm with mean percentage recoveries of 99.90±0.48 and 99.95±0.67, respectively. While second derivative spectrophotometry (D2) was used for determination of drug in presence of alkaline degradation products. Second method is first-derivative of the ratio spectra (DR1) for determination of OLA in presence of its acidic and alkaline degradation products at 267.9 and 251.6 nm, respectively with mean percentage recoveries of 99.81±0.64 and 100.53±1.11, respectively. The third method is pH-induced difference method for determination of OLA in presence of its acidic and alkaline degradation products; with mean percentage recoveries 100.09±0.06 and 99.77±0.78, respectively. Fourth method is the Q-analysis (absorption ratio) method, which involves the formation of absorbance equation at 296.3 nm (isosbestic point) and 271 nm (λmax of OLA) for the determination of OLA in presence of its acidic degradation products. The mean percentage recovery is 100.07±1.51. Fifth method based on dual wavelength selection was developed for the determination of OLA in presence of its acidic degradation products with mean percentage recovery of 100.36±0.69. Sixth method based on simple mathematic algorithm by the bivariate calibration was also used for the determination of OLA with the mean percentage recovery of 101.72±1.10. The second technique is chemometrics, which includes determination of OLA in presence of its acidic degradation products using multivariate calibration methods (the classical least squares (CLS), principle component regression (PCR) and partial least squares (PLS)) using the information contained in the absorption spectra.